2021
DOI: 10.1038/s41419-021-03765-x
|View full text |Cite
|
Sign up to set email alerts
|

Kartogenin prevents cartilage degradation and alleviates osteoarthritis progression in mice via the miR-146a/NRF2 axis

Abstract: Osteoarthritis (OA) is a common articular degenerative disease characterized by loss of cartilage matrix and subchondral bone sclerosis. Kartogenin (KGN) has been reported to improve chondrogenic differentiation of mesenchymal stem cells. However, the therapeutic effect of KGN on OA-induced cartilage degeneration was still unclear. This study aimed to explore the protective effects and underlying mechanisms of KGN on articular cartilage degradation using mice with post-traumatic OA. To mimic the in vivo arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…IL-1β could significantly restrain the synthesis of collagen II and enhanced of inflammatory factors, such as iNOS and COX2. Previous studies reported that the stimulation of IL-1β (10 ng/ml) for 24 h could induce inflammation in chondrocytes ( Huang et al, 2019 ; Hou et al, 2021 ). In this study, IL-1β (10 ng/ml) induced inflammatory responses in mouse chondrocytes indeed.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β could significantly restrain the synthesis of collagen II and enhanced of inflammatory factors, such as iNOS and COX2. Previous studies reported that the stimulation of IL-1β (10 ng/ml) for 24 h could induce inflammation in chondrocytes ( Huang et al, 2019 ; Hou et al, 2021 ). In this study, IL-1β (10 ng/ml) induced inflammatory responses in mouse chondrocytes indeed.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis and GO functional enrichment of up-regulated DEGs results ( Fig. 6 C1, D1, Table S2A ) found that several cartilage-related pathways and bioprocesses, as well as cartilage-specific genes (COL II, ACAN, and SOX9), were significantly activated, such as the MAPK signaling pathway [ [51] , [52] , [53] ], cartilage development, glycosaminoglycan biosynthetic process, and negative regulation of smooth muscle cell proliferation. These signaling pathways, bioprocesses, and specific genes were related to the positive regulation of the chondrogenic differentiation, cartilage development, ECM synthesis, and negative regulation of angiogenesis, implying that ACM powder promoted chondrogenic differentiation and cartilage regeneration of BMSCs and inhibited the development of blood vessel, which benefited enhancing the stability of BMSC-regenerated cartilage.…”
Section: Resultsmentioning
confidence: 99%
“…Strengthening the Nrf2-HO-1 pathway not only alleviates OA-related oxidative stress injury but also bene ts ECM anabolic metabolism to protect against OA. A possible upstream mediator of Nrf2 was revealed to be microRNA (miRNA)-146a-5p, which targets the 3' untranslated region (3'UTR) of Nrf2 to block its translational process [27]. Indeed, the other miRNAs are considered potential regulators of Nrf2, such as miR-132 [28], miR-27a [29], or miR-3175 [30], some of which may be targets of ARB but need further corroboration.…”
Section: Discussionmentioning
confidence: 99%